Adding Compost to Oil Palm Planting Holes can Increase the Diversity of Soil Fungi without Significantly Affecting the Gas Emissions on Wetlands - Hasrul Satria Nur; Abdul Hadi; Rindang Yuliani (Center for Journal Management and Publication, 2019)
The use of chemical fertilizers have been negative impact on environment, especially in increased the gas emissions and reduced the diversity of microbes, such as bacteria, actinomycetes, and soil fungi. As the one of the alternatively is used the combined compost. For instance, grass compost with the added of inorganic fertilizer (chemical), oil palm empty fruit bunches compost with the added of inorganic fertilizer, and the inorganic fertilizer without compost. The measuring of gas emissions was carried out on CH4, CO2 and N2O at several of the oil palm planting holes. Every sample gases were collected by the chambers installed with syringe. .Thus, the gas emissions were analyzed by chromatography gas type GHG 450 Shimadzu. Besides that, the diversity of soil fungi were also determined by the characterization and identification. The result of this research showed of reducting on CH4 that was appplied by the combined of oil palm empty fruit bunch compost with inorganic fertilizers i.e., 0.019 until-0.316 g CH4.m-2.h-1. The same patterns were also demonstrated by CO2 from the treament of oil palm empty fruit bunch with inorganic fertilizers, viz 755.246 untill-2.331 g CO2.m-2.h-1. Relating to N2O, it has undergone reduced by grass compost with inorganic fertilizers, viz-27.726 until-25.622 mg N2O.m-2.h-1 . Meanwhile, the genera of soil fungi that were found on the sites after applying combining compost, viz Aspergillus, Bipolaris, Gonatobotrys, Gonatorrhodiella, Oidiodendron, Penicillium, Rhynchosporium, Rhizopus, Trichoderma, and Trichocladium. Therefore, the use of compost with combining chemical fertilizers are potentially to apply into the oil palm field on wetlands.